ASPECTS OF PRECOLONIAL ISOKO SOCIO-POLITICAL RELATIONS WITH THEIR NEIGHBOURS IN SOUTH CENTRAL NIGERIA - Okpevra, Uwomano Benjamin (International Review of Humanities Studies, 2020)
This work focused on aspects of pre-colonial Isoko socio-political relations with their neighbours in the Niger Delta region of South Central Nigeria. It attempts to illuminate the nexus between internal and external dynamics and the concomitant changes and continuities in Isoko relations with their Urhobo, Ijaw, Ukwuani and Aboh neighbours. The work is premised on the historical method and interpretations deploying primary and secondary data to achieve its objective. The study concludes that intergroup relations in the region is largely influenced by their somewhat common ancestral origin; geographical contiguity; a shared common environmental and cultural practices; and the experience of similar external influences. This is done within the context of contemporary trajectory of the socio-political conflicts in the Niger Delta with serious implications for both National and International interests.